Effect of morphine on cerebral activity of extremely premature infants. (December 2020) - Peled, Miriam; Abuhatzira, Avishag; Novack, Lena; Meledin, Irina; Shany, Eilon
Abstract: Background: Morphine is widely used for sedation in premature infants and may have long-term effects on neurodevelopmental outcome. Aims: To assess its effect on cerebral activity of extremely preterm infants. Methods: Retrospective study in infants less than 28 weeks of gestational age (GA), treated with morphine and monitored with amplitude integrated EEG (aEEG), that were assessed at baseline and 6 consecutive 2 h periods. At each period, the background activity score and presence of cycling were determined. Results: A total of 140 infants were included. Background aEEG activity score worsened in 40% of the infants by 6 h after morphine initiation and cycling, initially present in 70% of the infants, could be detected in only 10% after 10 h. On multivariable analysis, adjusted for baseline aEEG score and GA, the background activity decreased by 0.85 (95% confidence interval (CI): 0.74–0.97) immediately after morphine initiation, 0.72 (CI: 0.63–0.83) at 2 h later and on average by 0.64 (CI: 0.57–0.71) at each subsequent 2 h periods. The relative risk of cycling loss at 2 h and 4 h after morphine administration was 1.58 (CI: 1.15–2.16) and 3.37 (CI: 2.23–5.08), respectively. Conclusions: Continuous infusion of morphine in extremely preterm infants significantly depresses their cerebral activity soon after its commencement. Highlights: Morphine affects the normal architecture of cerebral activity in extremely premature infants. Both background pattern and cycling are suppressed by continuous infusion of morphine. Changes in cerebral function can be detected in the first hours after the initiation of morphine. aEEG can be used to follow the effect of morphine on cerebral function in extremely premature infants.